Two-component polyurethane adhesive and preparation method thereof
By developing a solvent-free two-component polyurethane adhesive, using oligomer polyol and other ingredients for room temperature curing, the existing adhesives have been solved in terms of water resistance and bonding properties, and high-performance, environmentally friendly and easy-to-operate adhesives are achieved.
Patent Information
- Application Number
- CN202411980397.5
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-12-31
- Publication Date
- 2025-03-18
AI Technical Summary
Existing two-component polyurethane adhesives are difficult to meet the needs of high performance, environmental protection and ease of operation under certain operating conditions, especially in terms of water resistance and bonding properties.
A solvent-free two-component polyurethane adhesive was developed, and the A and B were mixed at a certain proportion of room temperature by synthesizing component A, defoaming, applied to the surface of the bonded material, compacted in both phases, and cured at room temperature to complete the bonding. The adhesive uses oligomer polyols, crosslinking agents, coupling agents, adhesive enhancers and fillers to ensure its moderate viscosity and good curing properties during the bonding process.
It has achieved high-performance polyurethane adhesive with strong environmental protection, room temperature curing, adjustable curing speed, excellent mechanical properties, easy operation and good water resistance. It is suitable for various polymer plastics, wood, glass, metal and other substrates.
Smart Images

Figure SMS_1 
Figure SMS_2 
Figure SMS_3
Abstract
Description
Technical Field
[0001] The invention belongs to the technical field of adhesives, and in particular relates to a two-component polyurethane adhesive and a preparation method thereof. Background Art
[0002] Two-component polyurethane adhesives have the characteristics of adjustable hardness, high bonding strength, controllable curing time, wide range of bonding substrates, excellent low-temperature flexibility and high peel strength, etc., and are widely used in aerospace, construction engineering, wood processing and medical and health fields. However, in practical applications, especially in some specific working conditions, it is necessary to develop more high-performance, highly adaptable and environmentally friendly two-component polyurethane adhesives; Patent CN 117551416 A discloses a room temperature curing water-resistant polyurethane adhesive and a preparation method thereof. The water absorption rate of the water-resistant polyurethane adhesive provided by the invention is ≤0.5%, but its hardness is low and its viscosity is high, resulting in poor fluidity of the adhesive and inconvenient operation of construction and coating; Patent CN 117025155 A discloses a two-component polyurethane adhesive for outdoor yachts, which contains a catalyst and a solvent, causing environmental pollution.
[0003] Therefore, the research and development of high-performance polyurethane adhesives with good bonding properties, excellent water resistance and environmental protection to meet the needs of industrial production and daily life will have a broad market space. Summary of the invention
[0004] In view of this, the present invention provides a solvent-free two-component polyurethane adhesive with strong environmental protection, room temperature curing, adjustable curing speed, excellent mechanical properties, simple operation and good water resistance.
[0005] The technical problem to be solved by the present invention is achieved by the following technical solution, which includes the following steps: mixing the synthesized component A and component B in a certain proportion at room temperature, applying them on the surface of the bonding material after degassing, compacting the two phases, and curing at room temperature for a certain period of time to complete the bonding.
[0006] The polyurethane adhesive is made of the following raw materials in parts by weight: Preferably, the composition and weight proportion of component A are: 40-93 parts by weight of oligomer polyol; Cross-linking agent 0.1-20 parts by weight; 5-20 parts by weight of coupling agent; 5-20 parts by weight of tackifier; Filler I 2-18 parts by weight; Preferably, the composition and weight proportion of component B are: Prepolymer 45-98 parts by weight; 2-18 parts by weight of polymer; Filler II 2~55 parts by weight.
[0007] The prepolymer in the component B comprises the following components and their weight proportions are: Isocyanate 20-75 parts by weight; 18-74 parts by weight of oligomer polyol; Antioxidant 0.1~8 parts by weight; 0.1-5 parts by weight of ultraviolet light absorber; 0.1~5 parts by weight of water removal agent; Other additives 2~13 parts by weight.
[0008] The oligomer polyol in the component A is selected from one or more of polytetramethylene glycol (PTMG), polybutylene adipate (PBA), polycaprolactone polyol (PCL), hydroxy-terminated polybutadiene (HTPB) and its derivatives, hydroxy-terminated polybutadiene-acrylonitrile (HTBN), hydroxy-terminated styrene-butadiene liquid rubber (HTBS), polycarbonate diol (PCDL), polypropylene carbonate diol (PPCD), polyoxypropylene glycol (PPG), castor oil and its derivative polyol (CAS); The chain extender in the A component is selected from one or more of N,N-aniline diisopropyl alcohol (DIPA), 2-ethyl-1,3-hexanediol (EHD), 2-butyl-2-ethyl-1,3-propanediol (BEPG), 2,2,4-trimethyl-1,3-pentanediol (TMPD), low molecular weight polycaprolactone (PCL), 1,4-butanediol (BDO), 4,4'-diamino-3,3'-dichlorodiphenylmethane (MOCA), triethanolamine (TEA), ethylene glycol (EG), diethylene glycol (DEG), trimethylolpropane (TMP) and glycerol; The crosslinking agent in the A component is selected from one or more of glycerol, trimethylolpropane, 3,3'-dichloro-4,4'-diphenylmethanediamine (MOCA), 4,4'-bis-sec-butylaminodicyclohexylmethane, N,N-bisaminopropylmethylamine, ethylenediamine (EDA), triethylamine (TEA), propylenediamine, p-toluenesulfonyl chloride, diisopropyl peroxide, diacetone acrylamide, and low molecular weight polyether polyol; The coupling agent in the component A is selected from one or more of γ-aminopropyltriethoxysilane (KH-550), N-(β-aminoethyl)-γ-aminopropyltrimethoxysilane (KH792), N-(2-aminoethyl)-3-aminopropyltriethoxysilane (KH552), γ-glycidyloxypropyltrimethoxysilane (KH560), γ-mercaptopropyltrimethoxysilane (KH590), (meth) acrylic acid (ester) monomer, acrylonitrile, styrene, allyl alcohol, and hydroxymethylresorcinol (HMR) coupling agent; The tackifier in the component A is selected from one or more of ethylene-vinyl acetate copolymer (EVA), polysiloxane, polyacrylate, rosin resin, carboxyethyl cellulose, bentonite, liquid terpene resin, epoxy resin, liquid rosin methyl ester, associative polyether polyol, paraffin, microcrystalline wax, polyethylene wax, oxidized polyethylene wax, polypropylene wax, sasol wax, hyperbranched polymer, APAO, ethylene bisstearamide, urea, hydroxylamine hydrochloride, hydroxylamine sulfate, and cyclohexanol; The filler I in the component A is selected from one or more of carbon black, tetraethyl orthosilicate, tetrabutyl titanate, aluminum oxide, vanadium oxide, silicon dioxide, calcium oxide, calcium carbonate, kaolin, titanium dioxide, glass fiber, gypsum powder, wollastonite powder, talc powder, silica powder, barite powder and barium sulfate.
[0009] The isocyanate in the prepolymer is selected from one or more of diphenylmethane diisocyanate (TDI), diphenylmethane-4-4'-diisocyanate (MDI), isophorone diisocyanate (IPDI), p-phenylene diisocyanate (PPDI), xylylene diisocyanate (XDI), polymeric MDI, HDI trimer, IPDI trimer, HMDI trimer, triphenylmethane triisocyanate (TTI), polyphenyl polymethylene polyisocyanate (PAPI), etc.; The oligomer polyol is selected from one or more of polytetramethylene glycol (PTMG), polybutylene adipate (PBA), polycaprolactone polyol (PCL), hydroxyl-terminated polybutadiene (HTPB) and its derivatives, hydroxyl-terminated polybutadiene-acrylonitrile (HTBN), hydroxyl-terminated styrene-butadiene liquid rubber (HTBS), polycarbonate diol (PCDL), polypropylene carbonate diol (PPCD), polyoxypropylene glycol (PPG), castor oil and its derivative polyols (CAS); The antioxidant is selected from one or more of antioxidant 245, antioxidant 1010, antioxidant 1035, antioxidant 1076, antioxidant 1098, antioxidant 1135, antioxidant 1330, antioxidant 3114, antioxidant 1024, antioxidant 5057 and other main antioxidants; The ultraviolet light absorber is selected from one or more of ultraviolet light absorber UV-1, ultraviolet light absorber UV-320, ultraviolet light absorber UV326, ultraviolet light absorber UV-327, ultraviolet light absorber UV-327, ultraviolet light absorber UV-328, ultraviolet light absorber UV-571, ultraviolet light absorber UV-1130, light stabilizer 944, and light stabilizer 292; The dewatering agent is selected from one or more of carbodiimide and its derivatives, glycidyl ether epoxy compounds, oxazolidine dewatering agent, p-toluenesulfonyl isocyanate, triethyl orthoformate, calcium oxide, calcium carbonate, polyurethane multifunctional dewatering agent CUWR-WB50S, CUWR-WB20, etc.; The other auxiliary agents include one or more of a defoamer, a hydrolysis stabilizer, a bactericide and a mildew preventer, an antistatic agent, a deodorant and a plasticizer.
[0010] The polymer in the component B is selected from one or more of poly(meth)acrylic acid (ester), epoxy resin, polyvinyl chloride, and silicone; The filler II is selected from one or more of carbon black, tetraethyl orthosilicate, tetrabutyl titanate, aluminum oxide, vanadium oxide, silicon dioxide, calcium oxide, calcium carbonate, kaolin, titanium dioxide, glass fiber, gypsum powder, wollastonite powder, talc powder, silica powder, barite powder and barium sulfate.
[0011] The innovative features of the present invention are as follows: (1) The polyurethane adhesive of the present invention can be used for construction by mixing components A and B at room temperature in a certain proportion, achieving firm bonding, moderate mixed viscosity, easy glue application, and simple and practical; (2) It can be cured at room temperature, without the need for additional infrared heating or UV curing equipment, thus reducing energy consumption. It has the advantages of economy, low cost, high bonding strength and strong water resistance; (3) The polyurethane adhesive synthesized by the present invention is free of solvents and catalysts, and has the advantages of being environmentally friendly and safe, easy to store, transport and use; (4) The polyurethane adhesive synthesized by the present invention is suitable for a wide range of substrates, including: various polymer plastics, wood, glass, metal and other building materials.
[0012] The experimental results show that the present invention can stably improve the bonding performance of polyurethane adhesives. In the composite process of PVDF film and PET film, the peel strength is as high as 1.19N / mm; the mechanical properties are excellent, the tensile strength is as high as 15.25MPa, and the shear strength with the wood board is as high as 4.98MPa; the water resistance is good, and the water absorption rate is less than 0.2%. The water resistance and mechanical properties are better than those of ordinary polyurethane adhesives on the market. DETAILED DESCRIPTION In order to further understand the present invention, preferred embodiments of the present invention are described below in conjunction with examples. However, it should be understood that these descriptions are only for further illustrating the features and advantages of the present invention, rather than limiting the claims of the present invention.
[0014] All raw materials of the present invention have no particular limitation on their sources, and can be purchased from the market or prepared according to conventional methods known to those skilled in the art.
[0015] There is no particular restriction on the purity of all raw materials in the present invention. The present invention preferably uses industrial purity or conventional purity used in the field of polyurethane adhesive preparation.
[0016] All noun expressions, abbreviations and trademarks in the present invention are conventional noun expressions, abbreviations and trademarks in the field. Each noun expression, abbreviation and trademark is clear and unambiguous in its relevant application field, and those skilled in the art can clearly, accurately and uniquely understand it based on the noun expressions, abbreviations and trademarks.
[0017] The invention provides a solvent-free two-component polyurethane adhesive which has strong environmental protection, room temperature curing, adjustable curing speed, excellent mechanical properties, simple operation and excellent water resistance.
[0018] The technical problem to be solved by the present invention is achieved by the following technical solution, which includes the following steps: mixing the synthesized component A and component B in a certain proportion at room temperature, applying them on the surface of the bonding material after degassing, compacting the two phases, and curing at room temperature for a certain period of time to complete the bonding.
[0019] The present invention is to better ensure the improvement of the performance of the polyurethane adhesive, the polyurethane adhesive product, according to The raw materials preferably include: The composition and weight proportions of component A are: 40-93 parts by weight of oligomer polyol; Cross-linking agent 0.1-20 parts by weight; 5-20 parts by weight of coupling agent; 5-20 parts by weight of tackifier; Filler I 2-18 parts by weight; The composition and weight proportions of component B are: Prepolymer 45-98 parts by weight; 2-18 parts by weight of polymer; Filler II 2~55 parts by weight.
[0020] The prepolymer in the component B comprises the following components and their weight proportions are: Isocyanate 20-75 parts by weight; 18-74 parts by weight of oligomer polyol; Antioxidant 0.1~8 parts by weight; 0.1-5 parts by weight of ultraviolet light absorber; 0.1~5 parts by weight of water removal agent; Other additives 2~13 parts by weight.
[0021] In the present invention, the weight portion of the oligomer polyol in the component A is preferably 60 to 90 parts by weight.
[0022] In the present invention, the weight portion of the crosslinking agent in the component A is preferably 10 to 15 weight portions.
[0023] In the present invention, the weight parts of the coupling agent in the component A is preferably 5 to 15 weight parts.
[0024] In the present invention, the weight portion of the tackifier in the component A is preferably 5 to 15 weight portions.
[0025] In the present invention, the weight portion of filler I in component A is preferably 5 to 10 weight portions.
[0026] In the present invention, the weight portion of the prepolymer in the B component is preferably 75 to 90 parts by weight.
[0027] In the present invention, the weight portion of the polymer in the B component is preferably 5 to 15 weight portions.
[0028] In the present invention, the weight portion of filler II in the B component is preferably 5 to 25 weight portions.
[0029] In the present invention, the weight portion of isocyanate in the prepolymer in component B is preferably 55 to 70 parts by weight.
[0030] In the present invention, the weight portion of the oligomer polyol in the prepolymer in the B component is preferably 30 to 60 parts by weight.
[0031] In the present invention, the weight portion of the antioxidant in the prepolymer in the B component is preferably 0.3 to 5 parts by weight.
[0032] In the present invention, the weight portion of the ultraviolet light absorber in the prepolymer in the B component is preferably 0.5 to 3 parts by weight.
[0033] In the present invention, the weight portion of the water scavenger in the prepolymer in the B component is preferably 0.5 to 3 parts by weight.
[0034] In the present invention, the weight portion of other additives in the prepolymer in the B component is preferably 5 to 10 weight portions, more preferably, the weight portion of the defoamer is preferably 0.1 to 0.5 weight portion, the weight portion of the hydrolysis stabilizer is preferably 0.1 to 2 weight portions, the weight portion of the bactericidal and mildewproof agent is preferably 0.01 to 1 weight portion, the weight portion of the plasticizer is preferably 0.1 to 3 weight portions, and the weight portion of the deodorant is preferably 0.01 to 1 weight portion.
[0035] In the present invention, the oligomer polyol in the component A preferably includes one or more of polytetramethylene glycol (PTMG), polybutylene adipate (PBA), polycaprolactone polyol (PCL), hydroxyl-terminated polybutadiene (HTPB) and its derivatives, hydroxyl-terminated polybutadiene-acrylonitrile (HTBN), hydroxyl-terminated styrene-butadiene liquid rubber (HTBS), polycarbonate diol (PCDL), polypropylene carbonate diol (PPCD), polyoxypropylene glycol (PPG), castor oil and its derivative polyol (CAS); The chain extender in the A component preferably includes one or more of N,N-aniline diisopropyl alcohol (DIPA), 2-ethyl-1,3-hexanediol (EHD), 2-butyl-2-ethyl-1,3-propanediol (BEPG), 2,2,4-trimethyl-1,3-pentanediol (TMPD), low molecular weight polycaprolactone (PCL), 1,4-butanediol (BDO), 4,4'-diamino-3,3'-dichlorodiphenylmethane (MOCA), triethanolamine (TEA), ethylene glycol (EG), diethylene glycol (DEG), trimethylolpropane (TMP) and glycerol; The crosslinking agent in the A component preferably includes one or more of glycerol, trimethylolpropane, 3,3'-dichloro-4,4'-diphenylmethanediamine (MOCA), 4,4'-bis-sec-butylaminodicyclohexylmethane, N,N-bisaminopropylmethylamine, ethylenediamine (EDA), triethylamine (TEA), propylenediamine, p-toluenesulfonyl chloride, diisopropyl peroxide, diacetone acrylamide, and low molecular weight polyether polyol; The coupling agent in the A component preferably includes one or more of γ-aminopropyltriethoxysilane (KH-550), N-(β-aminoethyl)-γ-aminopropyltrimethoxysilane (KH792), N-(2-aminoethyl)-3-aminopropyltriethoxysilane (KH552), γ-glycidyloxypropyltrimethoxysilane (KH560), γ-mercaptopropyltrimethoxysilane (KH590), (meth) acrylic acid (ester) monomer, acrylonitrile, styrene, allyl alcohol, and hydroxymethylresorcinol (HMR) coupling agent; The tackifier in the A component preferably includes one or more of ethylene-vinyl acetate copolymer (EVA), polysiloxane, polyacrylate, rosin resin, carboxyethyl cellulose, bentonite, liquid terpene resin, epoxy resin, liquid rosin methyl ester, associative polyether polyol, paraffin, microcrystalline wax, polyethylene wax, oxidized polyethylene wax, polypropylene wax, sasol wax, hyperbranched polymer, APAO, ethylene bisstearic acid amide, urea, hydroxylamine hydrochloride, hydroxylamine sulfate, and cyclohexanol; The filler I in the A component preferably includes one or more of carbon black, tetraethyl orthosilicate, tetrabutyl titanate, aluminum oxide, vanadium oxide, silicon dioxide, calcium oxide, calcium carbonate, kaolin, titanium dioxide, glass fiber, gypsum powder, wollastonite powder, talc powder, silica powder, barite powder and barium sulfate.
[0036] The isocyanate in the prepolymer preferably includes one or more of diphenylmethane diisocyanate (TDI), diphenylmethane-4-4'-diisocyanate (MDI), isophorone diisocyanate (IPDI), p-phenylene diisocyanate (PPDI), xylylene diisocyanate (XDI), polymeric MDI, HDI trimer, IPDI trimer, HMDI trimer, triphenylmethane triisocyanate (TTI), polyphenyl polymethylene polyisocyanate (PAPI), etc.; The oligomer polyol preferably includes one or more of polytetramethylene glycol (PTMG), polybutylene adipate (PBA), polycaprolactone polyol (PCL), hydroxyl-terminated polybutadiene (HTPB) and its derivatives, hydroxyl-terminated polybutadiene-acrylonitrile (HTBN), hydroxyl-terminated styrene-butadiene liquid rubber (HTBS), polycarbonate diol (PCDL), polypropylene carbonate diol (PPCD), polyoxypropylene glycol (PPG), castor oil and its derivative polyol (CAS); The antioxidant preferably includes one or more of antioxidant 245, antioxidant 1010, antioxidant 1035, antioxidant 1076, antioxidant 1098, antioxidant 1135, antioxidant 1330, antioxidant 3114, antioxidant 1024, antioxidant 5057 and other main antioxidants; The ultraviolet light absorber preferably includes one or more of ultraviolet light absorber UV-1, ultraviolet light absorber UV-320, ultraviolet light absorber UV326, ultraviolet light absorber UV-327, ultraviolet light absorber UV-327, ultraviolet light absorber UV-328, ultraviolet light absorber UV-571, ultraviolet light absorber UV-1130, light stabilizer 944, and light stabilizer 292; The dewatering agent preferably includes one or more of carbodiimide and its derivatives, glycidyl ether epoxy compounds, oxazolidine dewatering agent, p-toluenesulfonyl isocyanate, triethyl orthoformate, calcium oxide, calcium carbonate, polyurethane multifunctional dewatering agent CUWR-WB50S, CUWR-WB20, etc.; The other auxiliary agents preferably include one or more of a defoaming agent, a hydrolysis stabilizer, a bactericide and a mildew preventer, an antistatic agent, a deodorant and a plasticizer.
[0037] The polymer in the component B preferably includes one or more of poly(meth)acrylic acid (ester), epoxy resin, polyvinyl chloride, and silicone; The filler II preferably includes one or more of carbon black, tetraethyl orthosilicate, tetrabutyl titanate, aluminum oxide, vanadium oxide, silicon dioxide, calcium oxide, calcium carbonate, kaolin, titanium dioxide, glass fiber, gypsum powder, wollastonite powder, talc powder, silica powder, barite powder and barium sulfate.
[0038] In order to further illustrate the present invention, a method for preparing a polyurethane adhesive provided by the present invention is described in detail below in combination with examples. However, it should be understood that these examples are implemented on the premise of the technical solution of the present invention, and detailed implementation methods and specific operating processes are given only to further illustrate the features and advantages of the present invention, rather than to limit the claims of the present invention, and the protection scope of the present invention is not limited to the following examples.
[0039] Test method: 1. Peel strength: Determined according to the national standard GB / T 2790-1995.
[0040] Tensile shear strength: measured according to national standard GB / T 7124-2008.
[0041] Hardness: Determined according to national standard GB / T 531.1-2008.
[0042] Determination of water absorption of plastics: Sample preparation and determination according to national standard GB / T 1034-2008. The water absorption of the film was evaluated by cutting the film into square flat test pieces with a side length of 100 mm and a thickness of 2.05 mm ± 0.05 mm. The cut film was immersed in water and the water absorption was evaluated for 7 consecutive days.
[0043] Example 1 (1) Preparation of polyurethane adhesive component A Add 60g of hydroxy-terminated polybutadiene-acrylonitrile with a molecular weight of 3000 and 18g of 1,4-butanediol into a three-necked flask, heat to 120°C, and stir to remove water under a vacuum environment with a vacuum degree of -0.09MPa for about 1~2h; then, cool the three-necked flask to 55°C, introduce nitrogen to release the vacuum environment, add 3.5g of trimethylolpropane, 3.5g of γ-mercaptopropyltrimethoxysilane, 3.5g of rosin resin, and 3g of white carbon black into the reactor, stir evenly at high speed, cool to room temperature, discharge the material, obtain component A, and seal it for later use.
[0044] (2) Preparation of polyurethane adhesive component B a. Add 30 g of hydroxy-terminated polybutadiene-acrylonitrile with a molecular weight of 3000 and 30 g of polytetrahydrofuran diol with a molecular weight of 650 into a three-necked flask, and evacuate and remove water at a temperature of 120 ° C until the system is free of bubbles and the water is completely removed; introduce nitrogen to release the vacuum environment, cool the kettle to 75 ° C, add 80 g of isophorone diisocyanate, continue to evacuate and stir for a reaction for 2 h, add about 1 g of antioxidant 1024, 1 g of ultraviolet light absorber UV-1130, and 1.2 g of carbodiimide, continue to evacuate and stir for a second reaction at high speed, and when the free NCO value of the mixture reaches the expected requirement, cool to 60 ° C to obtain the prepolymer, which is stored for later use.
[0045] b. Weigh 50 g of the above prepolymer into a mixing kettle, heat to 70 ° C, add 1.5 g of epoxy resin E-51 and 1.5 g of calcium oxide powder under nitrogen protection, stir evenly at high speed, cool to room temperature, discharge, obtain component B, and seal for standby use.
[0046] (3) Blending process Weigh the above-mentioned component A and component B in a weight ratio of 100:100, mix them evenly at room temperature, apply them on the surface of the bonding material after degassing, compact the two phases, and cure them at room temperature for 24 hours to complete the bonding.
[0047] Example 2 (1) Preparation of polyurethane adhesive component A Add 60 g of polytetrahydrofuran diol with a molecular weight of 1000 and 12 g of 1,4-butanediol into a three-necked flask, heat to 120°C, and stir to remove water under a vacuum environment with a vacuum degree of -0.09 MPa for about 1 to 2 hours; then, cool the three-necked flask to 55°C, introduce nitrogen to release the vacuum environment, add 5 g of trimethylolpropane, 3.5 g of γ-mercaptopropyltrimethoxysilane, 3.0 g of polysiloxane, and 3 g of white carbon black into the reactor, stir evenly at high speed, cool to room temperature, discharge, obtain component A, and seal for standby use.
[0048] (2) Preparation of polyurethane adhesive component B a. Add 30 g of polytetrahydrofuran diol with a molecular weight of 1000 and 30 g of polytetrahydrofuran diol with a molecular weight of 650 into a three-necked flask, evacuate and remove water at a temperature of 120 ° C until the system is free of bubbles and the water is removed cleanly; introduce nitrogen to release the vacuum environment, cool the kettle to 65 ° C, add 75 g of diphenylmethane-4-4'-diisocyanate, continue evacuating and stirring the reaction for 1.5 h, add about 1 g of antioxidant 1024, 1 g of ultraviolet light absorber UV-1130, and 1.2 g of carbodiimide, continue evacuating and stirring the reaction for a second time, and when the free NCO value of the mixture reaches the expected requirement, cool to 60 ° C to obtain a prepolymer, which is stored for later use.
[0049] b. Weigh 80 g of the above prepolymer into a mixing kettle, heat to 70 ° C, add 1.5 g of epoxy resin E-51 and 1.5 g of calcium oxide powder under nitrogen protection, stir evenly at high speed, cool to room temperature, discharge, obtain component B, and seal for standby use.
[0050] (3) Blending process Weigh the above-mentioned component A and component B in a weight ratio of 100:135, mix them evenly at room temperature, apply them on the surface of the bonding material after degassing, compact the two phases, and cure them at room temperature for 24 hours to complete the bonding.
[0051] Example 3 (1) Preparation of polyurethane adhesive component A Add 60g of poly(1,4-butylene adipate)diol with a molecular weight of 2000 and 6g of 1,4-butanediol into a three-necked flask, heat to 120°C, and stir to remove water under a vacuum environment with a vacuum degree of -0.09MPa for about 1~2h; then, cool the three-necked flask to 55°C, introduce nitrogen to release the vacuum environment, add 5g of trimethylolpropane, 3.5g of γ-mercaptopropyltrimethoxysilane, 3.0g of polysiloxane, and 3g of white carbon black into the reactor, stir evenly at high speed, cool to room temperature, discharge, obtain component A, and seal for standby use.
[0052] (2) Preparation of polyurethane adhesive component B a. Add 45g of poly(1,4-butylene adipate)diol with a molecular weight of 2000 and 30g of terminal hydroxyl polybutadiene with a molecular weight of 3000 into a three-necked flask, and remove water by vacuuming at 120°C until the system is free of bubbles and the water is completely removed; introduce nitrogen to release the vacuum environment, cool the kettle to 65°C, add 68.5g of diphenylmethane-4-4'-diisocyanate and 7g of polyphenyl polymethylene polyisocyanate, continue to vacuumize and stir for 1.5h, add about 1g of antioxidant 1024, 1g of ultraviolet light absorber UV-1130, and 1.2g of carbodiimide, continue to vacuumize and stir for a second time, and when the free NCO value of the mixture reaches the expected requirement, cool to 60°C to obtain the prepolymer, which is stored for later use.
[0053] b. Weigh 100 g of the above prepolymer into a mixing kettle, heat to 70 ° C, add 1.5 g of epoxy resin E-51 and 1.5 g of calcium oxide powder under nitrogen protection, stir at high speed, cool to room temperature, discharge, obtain component B, and seal for standby use.
[0054] (3) Blending process The above-mentioned component A and component B are weighed in a weight ratio of 100:180, mixed evenly at room temperature, applied on the surface of the bonding material after degassing, the two phases are compacted, and cured at room temperature for 24 hours to complete the bonding.
[0055] Example 4 (1) Preparation of polyurethane adhesive component A Add 60g of poly(1,4-butylene adipate)diol with a molecular weight of 2000 and 6g of 1,4-butanediol into a three-necked flask, heat to 120°C, and stir to remove water under a vacuum environment with a vacuum degree of -0.09MPa for about 1~2h; then, cool the three-necked flask to 55°C, introduce nitrogen to release the vacuum environment, add 5g of diethylene glycol, 3.5g of γ-aminopropyltriethoxysilane, 3.0g of polysiloxane, and 3g of white carbon black into the reactor, stir evenly at high speed, cool to room temperature, discharge, obtain component A, and seal for standby use.
[0056] (2) Preparation of polyurethane adhesive component B a. Add 60g of poly(1,4-butylene adipate)diol with a molecular weight of 2000 into a three-necked flask, and remove water by vacuuming at 120°C until the system is free of bubbles and the water is completely removed; introduce nitrogen to release the vacuum environment, cool the kettle to 75°C, add 77g of HMDI trimer, continue to vacuumize and stir for 2h, add about 1g of antioxidant 1024, 1g of ultraviolet light absorber UV-1130, and 1.2g of carbodiimide, continue to vacuumize and stir for a second time, and when the free NCO value of the mixture reaches the expected requirement, cool to 60°C to obtain the prepolymer, which is stored for later use.
[0057] b. Weigh 100 g of the above prepolymer into a mixing kettle, heat to 70 ° C, add 1.5 g of epoxy resin E-51 and 1.5 g of calcium oxide powder under nitrogen protection, stir at high speed, cool to room temperature, discharge, obtain component B, and seal for standby use.
[0058] (3) Blending process The above-mentioned component A and component B are weighed in a weight ratio of 100:150, mixed evenly at room temperature, applied on the surface of the bonding material after degassing, the two phases are compacted, and cured at room temperature for 48 hours to complete the bonding.
[0059] Example 5 (1) Preparation of polyurethane adhesive component A Add 80g of polycarbonate diol with a molecular weight of 2000 and 10g of 2-ethyl-1,3-hexanediol into a three-necked flask, heat to 120°C, and stir to remove water under a vacuum environment with a vacuum degree of -0.09MPa for about 1~2h; then, cool the three-necked flask to 55°C, introduce nitrogen to release the vacuum environment, add 5g of triethylamine, 3.5g of γ-mercaptopropyltrimethoxysilane, 3.0g of polysiloxane, and 3g of white carbon black into the reactor, stir evenly at high speed, cool to room temperature, discharge the material, obtain component A, and seal it for later use.
[0060] (2) Preparation of polyurethane adhesive component B a. Add 30g of 2000 polycarbonate diol with a molecular weight of 2000 and 30g of terminal hydroxyl polybutadiene with a molecular weight of 3000 into a three-necked flask, and evacuate and remove water at a temperature of 120°C until the system is free of bubbles and the water is completely removed; introduce nitrogen to release the vacuum environment, cool the kettle to 65°C, add 68.7g of diphenylmethane-4-4'-diisocyanate and 8g of polyphenyl polymethylene polyisocyanate, continue evacuating and stirring for a reaction for 1.5h, add about 1g of antioxidant 245, 1g of ultraviolet light absorber UV-1130, and 1.2g of carbodiimide, continue evacuating and stirring for a second high-speed reaction, and when the free NCO value of the mixture reaches the expected requirement, cool to 60°C to obtain the prepolymer, which is stored for later use.
[0061] b. Weigh 100 g of the above prepolymer into a mixing kettle, heat to 70 ° C, add 1.5 g of methyl acrylate and 1.5 g of gypsum powder under nitrogen protection, stir at high speed, cool to room temperature, discharge, obtain component B, and seal for standby use.
[0062] (3) Blending process Weigh the above-mentioned component A and component B according to a weight ratio of 100:120, mix them evenly at room temperature, apply them on the surface of the bonding material after degassing, compact the two phases, and cure them at room temperature for 24 hours to complete the bonding.
[0063] Example 6 (1) Preparation of polyurethane adhesive component A Add 60g of polycaprolactone polyol with a molecular weight of 2000 and 18g of N,N-aniline diisopropanol into a three-necked flask, heat to 120°C, and stir to remove water under a vacuum environment with a vacuum degree of -0.09MPa for about 1~2h; then, cool the three-necked flask to 55°C, introduce nitrogen to release the vacuum environment, add 12g of diethylene glycol, 3.5g of γ-aminopropyltriethoxysilane, 3.0g of polysiloxane, and 3g of white carbon black into the reactor, stir evenly at high speed, cool to room temperature, discharge the material, obtain component A, and seal it for standby use.
[0064] (2) Preparation of polyurethane adhesive component B a. Add 50g of polycaprolactone polyol with a molecular weight of 2000 and 6g of terminal hydroxyl polybutadiene with a molecular weight of 3000 into a three-necked flask, and remove water by vacuuming at 120°C until the system is free of bubbles and the water is completely removed; introduce nitrogen to release the vacuum environment, cool the kettle to 65°C, add 68g of HMDI trimer, continue to vacuum and stir for 1.5h, add about 1g of antioxidant 1024, 1g of ultraviolet light absorber UV-1130, and 1.2g of carbodiimide, continue to vacuum for a second high-speed stirring reaction, and when the free NCO value of the mixture reaches the expected requirement, cool to 60°C to obtain the prepolymer, which is stored for later use.
[0065] b. Weigh 100 g of the above prepolymer into a mixing kettle, heat to 70 ° C, add 1.5 g of silicone resin and 1.5 g of calcium oxide powder under nitrogen protection, stir at high speed, cool to room temperature, discharge, obtain component B, and seal for standby use.
[0066] (3) Blending process The above-mentioned component A and component B are weighed in a weight ratio of 100:150, mixed evenly at room temperature, applied to the surface of the bonding material after degassing, the two phases are compacted, and cured at room temperature for 12 hours to complete the bonding.
[0067] Example 7 (1) Preparation of polyurethane adhesive component A Add 60g of 2000 molecular weight hydroxy-terminated styrene butadiene liquid rubber and 10g of N,N-aniline diisopropanol into a three-necked flask, heat to 120°C, and stir to remove water under a vacuum environment with a vacuum degree of -0.09MPa for about 1~2h; then, cool the three-necked flask to 55°C, introduce nitrogen to release the vacuum environment, add 6g of diethylene glycol, 3.5g of γ-glycidyloxypropyltrimethoxysilane, 3.0g of polysiloxane, and 3g of white carbon black into the reactor, stir evenly at high speed, cool to room temperature, discharge, obtain component A, and seal for standby use.
[0068] (2) Preparation of polyurethane adhesive component B a. Add 50g of 2000 molecular weight hydroxy-terminated styrene butadiene liquid rubber into a three-necked flask, and remove water by vacuuming at 120°C until the system is free of bubbles and the water is completely removed; introduce nitrogen to release the vacuum environment, cool the kettle to 65°C, add 72g of diphenylmethane diisocyanate, continue to vacuumize and react with stirring for 1.5h, add about 1g of antioxidant 1024, 1g of ultraviolet light absorber UV-1130, and 1.2g of carbodiimide, continue to vacuumize and react with high-speed stirring for a second time, and when the free NCO value of the mixture reaches the expected requirement, cool to 60°C to obtain the prepolymer, which is stored for later use.
[0069] b. Weigh 100 g of the above prepolymer into a mixing kettle, heat to 70 ° C, add 1.5 g of silicone resin and 1.5 g of calcium oxide powder under nitrogen protection, stir at high speed, cool to room temperature, discharge, obtain component B, and seal for standby use.
[0070] (3) Blending process The above-mentioned component A and component B are weighed in a weight ratio of 100:130, mixed evenly at room temperature, applied on the surface of the bonding material after degassing, the two phases are compacted, and cured at room temperature for 48 hours to complete the bonding.
[0071] Example 8 (1) Preparation of polyurethane adhesive component A Add 60g of polyoxypropylene glycol with a molecular weight of 3000 and 6g of N,N-aniline diisopropanol into a three-necked flask, heat to 120°C, and stir to remove water under a vacuum environment with a vacuum degree of -0.09MPa for about 1~2h; then, cool the three-necked flask to 55°C, introduce nitrogen to release the vacuum environment, add 6g of 2-ethyl-1,3-hexanediol, 5g of γ-glycidyloxypropyltrimethoxysilane, 5g of polysiloxane, and 3g of white carbon black into the reactor, stir evenly at high speed, cool to room temperature, discharge the material, obtain component A, and seal it for standby use.
[0072] (2) Preparation of polyurethane adhesive component B a. Add 53g of polyoxypropylene glycol with a molecular weight of 3000 into a three-necked flask, evacuate and remove water at a temperature of 120°C until the system is free of bubbles and the water is completely removed; introduce nitrogen to release the vacuum environment, cool the kettle to 65°C, add 8g of diphenylmethane diisocyanate and 72g of polyphenyl polymethylene polyisocyanate, continue evacuating and stirring for a reaction for 1.5h, add about 1g of antioxidant 1024, 1g of ultraviolet light absorber UV-1130, 1.2g of carbodiimide, and 1.5g of dimethyl terephthalate, continue evacuating and stirring for a second time, and when the free NCO value of the mixture reaches the expected requirement, cool to 60°C to obtain the prepolymer, which is stored for later use.
[0073] b. Weigh 100 g of the above prepolymer into a mixing kettle, heat to 70 ° C, add 1.5 g of silicone resin and 1.5 g of calcium oxide powder under nitrogen protection, stir at high speed, cool to room temperature, discharge, obtain component B, and seal for standby use.
[0074] (3) Blending process Weigh the above-mentioned component A and component B in a weight ratio of 100:70, mix them evenly at room temperature, apply them on the surface of the bonding material after degassing, compact the two phases, and cure them at room temperature for 48 hours to complete the bonding.
[0075] Example 9 (1) Preparation of polyurethane adhesive component A Add 80g of polytetrahydrofuran diol with a molecular weight of 1000 and 6g of triethanolamine into a three-necked flask, heat to 120°C, and stir to remove water under a vacuum environment with a vacuum degree of -0.09MPa for about 1~2h; then, cool the three-necked flask to 55°C, introduce nitrogen to release the vacuum environment, add 6g of 2,2,4-trimethyl-1,3-pentanediol, 5g of γ-glycidyloxypropyltrimethoxysilane, 5g of polysiloxane, and 3g of white carbon black into the reactor, stir evenly at high speed, cool to room temperature, discharge, obtain component A, and seal for standby use.
[0076] (2) Preparation of polyurethane adhesive component B a. Add 44.3 g of polytetrahydrofuran diol with a molecular weight of 1000 and 5 g of poly(1,4-butylene adipate) diol with a molecular weight of 3000 into a three-necked flask, and remove water by vacuuming at a temperature of 120 ° C until the system is free of bubbles and the water is removed cleanly; introduce nitrogen to release the vacuum environment, cool the kettle to 70 ° C, add 8 g of hexamethylene diisocyanate and 72 g of polyphenyl polymethylene polyisocyanate, continue to vacuumize and stir the reaction for 1.5 h, add about 1 g of antioxidant 1024, 1 g of ultraviolet light absorber UV-1130, 1.2 g of carbodiimide, and 1.5 g of dimethyl terephthalate, continue to vacuumize and stir the reaction for a second time, and when the free NCO value of the mixture reaches the expected requirement, cool to 60 ° C to obtain a prepolymer, which is stored for later use.
[0077] b. Weigh 100 g of the above prepolymer into a mixing kettle, heat to 70 ° C, add 1.5 g of silicone resin and 1.5 g of calcium oxide powder under nitrogen protection, stir at high speed, cool to room temperature, discharge, obtain component B, and seal for standby use.
[0078] (3) Blending process Weigh the above-mentioned component A and component B in a weight ratio of 100:90, mix them evenly at room temperature, apply them on the surface of the bonding material after degassing, compact the two phases, and cure them at room temperature for 48 hours to complete the bonding.
[0079] Example 10 (1) Preparation of polyurethane adhesive component A Add 80g of polypropylene carbonate diol with a molecular weight of 3000 and 20g of triethanolamine into a three-necked flask, heat to 120°C, and stir to remove water under a vacuum environment with a vacuum degree of -0.09MPa for about 1~2h; then, cool the three-necked flask to 55°C, introduce nitrogen to release the vacuum environment, add 6g of 2,2,4-trimethyl-1,3-pentanediol, 5g of γ-glycidyloxypropyltrimethoxysilane, 5g of polysiloxane, and 3g of white carbon black into the reactor, stir evenly at high speed, cool to room temperature, discharge, obtain component A, and seal for standby use.
[0080] (2) Preparation of polyurethane adhesive component B a. Add 44.3 g of polytetrahydrofuran diol with a molecular weight of 1000 and 5 g of polypropylene carbonate diol with a molecular weight of 3000 into a three-necked flask, and remove water by vacuuming at a temperature of 120 ° C until the system is free of bubbles and the water is removed cleanly; introduce nitrogen to release the vacuum environment, cool the kettle to 70 ° C, add 8 g of hexamethylene diisocyanate and 72 g of polyphenyl polymethylene polyisocyanate, continue to vacuumize and stir the reaction for 1.5 h, add about 1 g of antioxidant 1024, 1 g of ultraviolet light absorber UV-1130, 1.2 g of carbodiimide, and 1.5 g of liquid rosin methyl ester, continue to vacuumize and stir the reaction for a second time, and when the free NCO value of the mixture reaches the expected requirement, cool to 60 ° C to obtain a prepolymer, which is stored for later use.
[0081] b. Weigh 100 g of the above prepolymer into a mixing kettle, heat to 70 ° C, add 1.5 g of silicone resin and 2 g of tetrabutyl titanate under nitrogen protection, stir at high speed, cool to room temperature, discharge, obtain component B, and seal for standby use.
[0082] (3) Blending process Weigh the above-mentioned component A and component B in a weight ratio of 100:110, mix them evenly at room temperature, apply them on the surface of the bonding material after degassing, compact the two phases, and cure them at room temperature for 12 hours to complete the bonding.
[0083] Embodiment 11 (1) Preparation of polyurethane adhesive component A Add 60g of 2000 molecular weight hydroxy-terminated styrene butadiene liquid rubber and 10g of N,N-aniline diisopropanol into a three-necked flask, heat to 120°C, and stir to remove water under a vacuum environment with a vacuum degree of -0.09MPa for about 1~2h; then, cool the three-necked flask to 55°C, introduce nitrogen to release the vacuum environment, add 6g of diethylene glycol, 3.5g of γ-glycidyloxypropyltrimethoxysilane, 3.0g of polysiloxane, and 3g of white carbon black into the reactor, stir evenly at high speed, cool to room temperature, discharge, obtain component A, and seal for standby use.
[0084] (2) Preparation of polyurethane adhesive component B a. Add 50g of 2000 molecular weight hydroxy-terminated styrene butadiene liquid rubber, 5g of polyoxypropylene glycol PPG 206, and 5g of PPG 310 into a three-necked flask, and evacuate and remove water at 120°C until the system is free of bubbles and the water is completely removed; introduce nitrogen to release the vacuum environment, cool the kettle to 65°C, add 80g of diphenylmethane diisocyanate, continue evacuating and stirring for a reaction for 1.5h, add about 1g of antioxidant 1024, 1g of ultraviolet light absorber UV-1130, and 1.2g of carbodiimide, continue evacuating and stirring for a second reaction, and when the free NCO value of the mixture reaches the expected requirement, cool to 60°C to obtain the prepolymer, which is stored for later use.
[0085] b. Weigh 100 g of the above prepolymer into a mixing kettle, heat to 70 ° C, add 1.5 g of silicone resin and 1.5 g of fumed silica under nitrogen protection, stir at high speed, cool to room temperature, discharge, obtain component B, and seal for standby use.
[0086] (3) Blending process The above-mentioned component A and component B are weighed in a weight ratio of 100:200, mixed evenly at room temperature, applied on the surface of the bonding material after degassing, the two phases are compacted, and cured at room temperature for 48 hours to complete the bonding.
[0087] Example 12 (1) Preparation of polyurethane adhesive component A Add 60g of polycaprolactone polyol with a molecular weight of 1000 and 6g of 2-ethyl-1,3-hexanediol into a three-necked flask, heat to 120°C, and stir to remove water under a vacuum environment with a vacuum degree of -0.09MPa for about 1~2h; then, cool the three-necked flask to 55°C, introduce nitrogen to release the vacuum environment, add 6g of diethylene glycol, 3.5g of γ-glycidyloxypropyltrimethoxysilane, 3.0g of polysiloxane, and 3g of white carbon black into the reactor, stir evenly at high speed, cool to room temperature, discharge, obtain component A, and seal for standby use.
[0088] (2) Preparation of polyurethane adhesive component B a. Add 50g of 2-ethyl-1,3-hexanediol with a molecular weight of 1000 into a three-necked flask, and evacuate and remove water at a temperature of 120°C until the system is free of bubbles and the water is completely removed; introduce nitrogen to release the vacuum environment, cool the kettle to 65°C, add 70g of diphenylmethane diisocyanate and 7g of polyphenyl polymethylene polyisocyanate, continue evacuating and stirring for a reaction for 1.5h, add about 1g of antioxidant 1010, 1g of ultraviolet light absorber UV-327, and 1.2g of carbodiimide, continue evacuating and stirring for a second reaction at high speed, and when the free NCO value of the mixture reaches the expected requirement, cool to 60°C to obtain the prepolymer, which is stored for later use.
[0089] b. Weigh 100 g of the above prepolymer into a mixing kettle, heat to 70 ° C, add 1.5 g of polyvinyl chloride and 1.5 g of fumed silica under nitrogen protection, stir at high speed, cool to room temperature, discharge, obtain component B, and seal for standby use.
[0090] (3) Blending process The above-mentioned component A and component B are weighed in a weight ratio of 100:160, mixed evenly at room temperature, applied on the surface of the bonding material after degassing, the two phases are compacted, and cured at room temperature for 48 hours to complete the bonding.
[0091] Example 13 (1) Preparation of polyurethane adhesive component A Add 60g of castor oil-based polyester polyol with a molecular weight of 1000 and 6g of 1,4-butanediol into a three-necked flask, heat to 120°C, and stir to remove water under a vacuum environment with a vacuum degree of -0.09MPa for about 1~2h; then, cool the three-necked flask to 55°C, introduce nitrogen to release the vacuum environment, add 3g of glycerol, 3.5g of γ-glycidyloxypropyltrimethoxysilane, 3.0g of hydroxymethylresorcinol, and 3g of white carbon black into the reactor, stir evenly at high speed, cool to room temperature, discharge, obtain component A, and seal for standby use.
[0092] (2) Preparation of polyurethane adhesive component B a. Add 36.2 g of castor oil-based polyester polyol with a molecular weight of 1000 and 18 g of poly(1,4-butylene adipate) diol with a molecular weight of 3000 into a three-necked flask, and remove water by vacuuming at 120 °C until the system is free of bubbles and the water is removed cleanly; introduce nitrogen to release the vacuum environment, cool the kettle to 65 °C, add 70 g of diphenylmethane diisocyanate and 7 g of polyphenyl polymethylene polyisocyanate, continue to vacuumize and stir for 1.5 h, add about 1 g of antioxidant 1010, 1 g of ultraviolet light absorber UV-327, and 1.2 g of polyurethane multifunctional water remover CUWR - WB50S, continue to vacuumize and stir for a second time, and when the free NCO value of the mixture reaches the expected requirement, cool to 60 °C to obtain the prepolymer, which is stored for later use.
[0093] b. Weigh 100 g of the above prepolymer into a mixing kettle, heat to 70 ° C, add 1.5 g of polymethyl acrylate and 1.5 g of glass fiber under nitrogen protection, stir at high speed, cool to room temperature, discharge, obtain component B, and seal for standby use.
[0094] (3) Blending process The above-mentioned component A and component B are weighed in a weight ratio of 100:130, mixed evenly at room temperature, applied on the surface of the bonding material after degassing, the two phases are compacted, and cured at room temperature for 48 hours to complete the bonding.
[0095] Embodiment 14 (1) Preparation of polyurethane adhesive component A Add 60g of castor oil-based polyester polyol with a molecular weight of 1000 and 6g of trimethylolpropane into a three-necked flask, heat to 120°C, and stir to remove water under a vacuum environment with a vacuum degree of -0.09MPa for about 1~2h; then, cool the three-necked flask to 55°C, introduce nitrogen to release the vacuum environment, add 5g of triethylamine, 5g of allyl alcohol, 3.0g of ethylene-vinyl acetate copolymer, and 3g of white carbon black into the reactor, stir evenly at high speed, cool to room temperature, discharge the material, obtain component A, and seal it for standby use.
[0096] (2) Preparation of polyurethane adhesive component B a. Add 36.2 g of castor oil-based polyester polyol with a molecular weight of 1000 and 40 g of polytetrahydrofuran diol with a molecular weight of 2000 into a three-necked flask, and remove water by vacuum at 120 ° C until the system is free of bubbles and the water is removed cleanly; introduce nitrogen to release the vacuum environment, cool the kettle to 65 ° C, add 70 g of diphenylmethane diisocyanate and 7 g of polyphenyl polymethylene polyisocyanate, continue to vacuum and stir the reaction for 1.5 h, add about 1 g of antioxidant 1010, 1 g of ultraviolet light absorber UV-327, and 1.2 g of polyurethane multifunctional water remover CUWR - WB50S, continue to vacuum and stir the reaction for a second time, and when the free NCO value of the mixture reaches the expected requirement, cool to 60 ° C to obtain the prepolymer, which is stored for later use.
[0097] b. Weigh 100 g of the above prepolymer into a mixing kettle, heat to 70 ° C, add 1.5 g of polymethyl acrylate and 1.5 g of glass fiber under nitrogen protection, stir at high speed, cool to room temperature, discharge, obtain component B, and seal for standby use.
[0098] (3) Blending process Weigh the above-mentioned component A and component B in a weight ratio of 100:150, mix them evenly at room temperature, apply them on the surface of the bonding material after degassing, compact the two phases, and cure them at room temperature for 24 hours to complete the bonding.
[0099] Comparative Example 1 Patent CN 115612440 A A two-component solvent-free photovoltaic backplane adhesive and a preparation method thereof, the adhesive.
[0100] Comparative Example 2 CN 110343497 A A solvent-free polyurethane adhesive for photovoltaic backboard, its preparation method and photovoltaic backboard, and the adhesive.
[0101] The adhesive synthesized in the above example was bonded to substrates (PET film, PVDF film), and the bonded substrates were immersed in distilled water at 23° C. for 7 days, and the peel strength was tested respectively. The data are as follows:
[0102] The above synthesized adhesive was tested for shear strength on different substrates, and the data are as follows:
[0103] The above synthesized adhesive was tested for tensile strength on different substrates, and the data are as follows:
[0104] The Shore A hardness and water absorption test of the above synthesized adhesive film is carried out, and the data are as follows:
Claims
1. A polyurethane adhesive, comprising two components A and B; wherein the composition and weight proportions of component A are: 40-93 parts of oligomer polyol, 4-20 parts of chain extender, 0.1-20 parts of cross-linking agent, 5-20 parts of coupling agent, 5-20 parts of tackifier, 2-18 parts of filler I; wherein the composition and weight proportions of component B are: 45-98 parts of prepolymer, 2-18 parts of polymer, 2-55 parts of filler II.
2. The polyurethane adhesive according to claim 1, characterized in that: The prepolymer in the B component comprises the following ingredients and their weight proportions are: 20-75 parts of isocyanate, 18-74 parts of oligomer polyol, 0.1-8 parts of antioxidant, 0.1-5 parts of ultraviolet light absorber, 0.1-5 parts of water remover, and 0-13 parts of other additives.
3. The polyurethane adhesive according to claim 1, characterized in that: The oligomer polyol in the component A is selected from one or more of polytetramethylene glycol (PTMG), polybutylene adipate (PBA), polycaprolactone polyol (PCL), hydroxy-terminated polybutadiene (HTPB) and its derivatives, hydroxy-terminated polybutadiene-acrylonitrile (HTBN), hydroxy-terminated styrene-butadiene liquid rubber (HTBS), polycarbonate diol (PCDL), polypropylene carbonate diol (PPCD), polyoxypropylene glycol (PPG), castor oil and its derivative polyol (CAS); The chain extender in the A component is selected from one or more of N,N-aniline diisopropyl alcohol (DIPA), 2-ethyl-1,3-hexanediol (EHD), 2-butyl-2-ethyl-1,3-propanediol (BEPG), 2,2,4-trimethyl-1,3-pentanediol (TMPD), low molecular weight polycaprolactone (PCL), 1,4-butanediol (BDO), 4,4'-diamino-3,3'-dichlorodiphenylmethane (MOCA), triethanolamine (TEA), ethylene glycol (EG), diethylene glycol (DEG), trimethylolpropane (TMP) and glycerol; The crosslinking agent in the A component is selected from one or more of glycerol, trimethylolpropane, 3,3'-dichloro-4,4'-diphenylmethanediamine (MOCA), 4,4'-bis-sec-butylaminodicyclohexylmethane, N,N-bisaminopropylmethylamine, ethylenediamine (EDA), triethylamine (TEA), propylenediamine, p-toluenesulfonyl chloride, diisopropyl peroxide, diacetone acrylamide, and low molecular weight polyether polyol; The coupling agent in the component A is selected from one or more of γ-aminopropyltriethoxysilane (KH-550), N-(β-aminoethyl)-γ-aminopropyltrimethoxysilane (KH792), N-(2-aminoethyl)-3-aminopropyltriethoxysilane (KH552), γ-glycidyloxypropyltrimethoxysilane (KH560), γ-mercaptopropyltrimethoxysilane (KH590), (meth) acrylic acid (ester) monomer, acrylonitrile, styrene, allyl alcohol, and hydroxymethylresorcinol (HMR) coupling agent; The tackifier in the component A is selected from one or more of ethylene-vinyl acetate copolymer (EVA), polysiloxane, polyacrylate, rosin resin, carboxyethyl cellulose, bentonite, liquid terpene resin, epoxy resin, liquid rosin methyl ester, associative polyether polyol, paraffin, microcrystalline wax, polyethylene wax, oxidized polyethylene wax, polypropylene wax, sasol wax, hyperbranched polymer, APAO, ethylene bisstearamide, urea, hydroxylamine hydrochloride, hydroxylamine sulfate, and cyclohexanol; The filler I in the component A is selected from one or more of carbon black, tetraethyl orthosilicate, tetrabutyl titanate, aluminum oxide, vanadium oxide, silicon dioxide, calcium oxide, calcium carbonate, kaolin, titanium dioxide, glass fiber, gypsum powder, wollastonite powder, talc powder, silica powder, barite powder and barium sulfate.
4. The polyurethane adhesive according to claim 2, characterized in that: The isocyanate in the prepolymer is selected from one or more of diphenylmethane diisocyanate (TDI), diphenylmethane-4-4'-diisocyanate (MDI), isophorone diisocyanate (IPDI), p-phenylene diisocyanate (PPDI), xylylene diisocyanate (XDI), polymeric MDI, HDI trimer, IPDI trimer, HMDI trimer, triphenylmethane triisocyanate (TTI), polyphenyl polymethylene polyisocyanate (PAPI), etc.; The oligomer polyol is selected from one or more of polytetramethylene glycol (PTMG), polybutylene adipate (PBA), polycaprolactone polyol (PCL), hydroxyl-terminated polybutadiene (HTPB) and its derivatives, hydroxyl-terminated polybutadiene-acrylonitrile (HTBN), hydroxyl-terminated styrene-butadiene liquid rubber (HTBS), polycarbonate diol (PCDL), polypropylene carbonate diol (PPCD), polyoxypropylene glycol (PPG), castor oil and its derivative polyols (CAS); The antioxidant is selected from one or more of antioxidant 245, antioxidant 1010, antioxidant 1035, antioxidant 1076, antioxidant 1098, antioxidant 1135, antioxidant 1330, antioxidant 3114, antioxidant 1024, antioxidant 5057 and other main antioxidants; The ultraviolet light absorber is selected from one or more of ultraviolet light absorber UV-1, ultraviolet light absorber UV-320, ultraviolet light absorber UV326, ultraviolet light absorber UV-327, ultraviolet light absorber UV-327, ultraviolet light absorber UV-328, ultraviolet light absorber UV-571, ultraviolet light absorber UV-1130, light stabilizer 944, and light stabilizer 292; The dewatering agent is selected from one or more of carbodiimide and its derivatives, glycidyl ether epoxy compounds, oxazolidine dewatering agent, p-toluenesulfonyl isocyanate, triethyl orthoformate, calcium oxide, calcium carbonate, polyurethane multifunctional dewatering agent CUWR-WB50S, CUWR-WB20; The other additives may include one or more of a defoamer, a hydrolysis stabilizer, a bactericide and a mildew preventer, an antistatic agent, a deodorant and a plasticizer.
5. The polyurethane adhesive according to claim 1, characterized in that: The polymer in component B is selected from one or more of poly(meth)acrylic acid (ester), epoxy resin, polyvinyl chloride, and silicone; The filler II is selected from one or more of carbon black, tetraethyl orthosilicate, tetrabutyl titanate, aluminum oxide, vanadium oxide, silicon dioxide, calcium oxide, calcium carbonate, kaolin, titanium dioxide, glass fiber, gypsum powder, wollastonite powder, talc powder, silica powder, barite powder and barium sulfate.
6. The polyurethane adhesive according to claims 1 to 5, characterized in that: The preparation method of the prepolymer in component B is: Weigh the oligomer polyol into a reaction kettle, evacuate and remove water at 100-140 ℃ until there are no bubbles in the system and the water is completely removed; cool the kettle to 55-90 ℃, add isocyanate, antioxidant, ultraviolet light absorber, water remover and filler II, stir at high speed, and when the free NCO value of the mixture reaches the expected requirement, cool it to room temperature to obtain the prepolymer.
7. The polyurethane adhesive according to claims 1 to 6, characterized in that: The preparation method of the component A is as follows: weighing oligomer polyol and chain extender into a reaction kettle, vacuuming and removing water at a temperature of 100-140° C. until the system is free of bubbles and the water is completely removed; cooling the kettle to 55-90° C., adding a crosslinking agent, a coupling agent, a tackifier, and a filler I, stirring evenly at a high speed, cooling to room temperature, discharging the material, obtaining the component A, and sealing for later use.
8. The polyurethane adhesive according to claims 1 to 7, characterized in that: The preparation method of the B component is as follows: weigh the prepolymer and add it into a mixing kettle, heat it to 60-80° C., add the polymer and filler II under nitrogen protection, stir evenly at high speed, cool it to room temperature, discharge the material, obtain the B component, and seal it for later use.
9. The polyurethane adhesive according to claim 1-8, wherein the method of using the polyurethane adhesive is as follows: component A and component B are mixed uniformly at room temperature in a weight ratio of 100:(70-255), applied to the surface of the bonding material after degassing, the two phases are compacted, and cured at room temperature for 1-48 hours to complete bonding.